2020
DOI: 10.3389/fmicb.2020.01622
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Aridity Gradient Modulates the Diversity of the Rhizosphere and Endosphere Bacterial Microbiomes of Opuntia ficus-indica

Abstract: Recent microbiome research has shown that soil fertility, plant-associated microbiome, and crop production can be affected by abiotic environmental parameters. The effect of aridity gradient on rhizosphere-soil (rhizosphere) and endosphere-root (endosphere) prokaryotic structure and diversity associated with cacti remain poorly investigated and understood. In the current study, next-generation sequencing approaches were used to characterize the diversity and composition of bacteria and archaea associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 76 publications
1
14
1
Order By: Relevance
“…Proteobacteria are dominant microbial communities in the rhizosphere and of numerous plants, and its various metabolic functions play an important role in maintaining the ecological balance of the soil, especially the abundance of nitrogen‐fixing bacteria (Le Quéré et al, 2021; Pang et al, 2021). Besides, Acidobacteria, Actinobacteria, Bacteroidetes and Cyanobacteria also have a great potential for rhizosphere ecology balance, nutrient cycling and the growth and adaptability of plant (Karray et al, 2020; Kaushik et al, 2021; Rocha et al, 2010). The abundant endophytic bacteria and fungi in the endosphere of D. officinale have been reported to have the function of antibacterial activity, promotion of nutrient absorption and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Proteobacteria are dominant microbial communities in the rhizosphere and of numerous plants, and its various metabolic functions play an important role in maintaining the ecological balance of the soil, especially the abundance of nitrogen‐fixing bacteria (Le Quéré et al, 2021; Pang et al, 2021). Besides, Acidobacteria, Actinobacteria, Bacteroidetes and Cyanobacteria also have a great potential for rhizosphere ecology balance, nutrient cycling and the growth and adaptability of plant (Karray et al, 2020; Kaushik et al, 2021; Rocha et al, 2010). The abundant endophytic bacteria and fungi in the endosphere of D. officinale have been reported to have the function of antibacterial activity, promotion of nutrient absorption and growth.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial composition is also reported to vary in different compartments of the model plants Arabidopsis thaliana (Bulgarelli et al, 2012 ), Populus spp. (Cregger et al, 2018 ), and Medicago truncatula (Brown et al, 2020 ), as well as those of the non‐model plants, such as Myrtillocactus geometrizans (Fonseca‐Garcia et al, 2016 ), Opuntia robusta (Fonseca‐Garcia et al, 2016 ), Cycas panzhihuaensis (Zheng & Gong, 2019 ), Agave spp (Coleman‐Derr et al, 2016 ), Boechera stricta (Wagner et al, 2016 ), and Opuntia ficus ‐ indica (Karray et al, 2020 ). The limited studies on the fungal phytobiomes have yielded similar results as the fungal composition was reported to be differentiated depending on plant compartments (Coleman‐Derr et al, 2016 ; Cregger et al, 2018 ; Fonseca‐Garcia et al, 2016 ; Gargouri et al, 2021 ; Zheng & Gong, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, arbuscular mycorrhizal fungi could mitigate the negative effect of future climate conditions by altering the community composition and enhancing the richness of specific taxa (Wahdan et al, 2021 ). Recent studies (Gargouri et al, 2021 ; Karray et al, 2020 ) performed on the genus Opuntia revealed that bacterial and fungal plant microbiomes changed in the rhizosphere and root endosphere along a climatic aridity gradient. Moreover, they identified specific biomarker taxa for each bioclimatic zone.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that environment patterned the extent of local adaptation between plants and rhizosphere biota, and the effects of plant-biota interactions on phenotypes. Going a step further, we also know that rhizosphere community composition and function commonly shift across climatic gradients (Veen et al, 2017;Van Nuland et al, 2017;Praeg et al, 2019;Karray et al, 2020;Vieira et al, 2020). As species colonize new habitats in response to global change, the turnover from locally adapted to novel species interactions may drive unexpected phenotypic changes and have implications for successful range shifts.…”
Section: Discussionmentioning
confidence: 99%